Self-Care as a Method to Cope With Suffering and Death: A Participatory Action-Research Aimed at Quality Improvement - Buonaccorso, Loredana; Tanzi, Silvia; Sacchi, Simona; Alquati, Sara; Bertocchi, Elisabetta; Autelitano, Cristina; Taberna, Eleonora; Martucci, Gianfranco (Frontiers in Psychology, 2022)
Introduction Palliative care is an emotionally and spiritually high-demanding setting of care. The literature reports on the main issues in order to implement self-care, but there are no models for the organization of the training course. We described the structure of training on self-care and its effects for a Hospital Palliative Care Unit. Method We used action-research training experience based mostly on qualitative data. Thematic analysis of data on open-ended questions, researcher’s field notes, oral and written feedback from the trainer and the participants on training outcomes and satisfaction questionnaires were used. Results Four major themes emerged: (1) “Professional role and personal feelings”; (2) “Inside and outside the team”; (3) “Do I listen to my emotions in the care relationship?”; (4) “Death: theirs vs. mine.” According to participants’ point of view and researchers’ observations, the training course resulted in ameliorative adjustments of the program; improved skills in self-awareness of own’s emotions and sharing of perceived emotional burden; practicing “compassionate presence” with patients; shared language to address previously uncharted aspects of coping; allowing for continuity of the skills learned; translation of the language learned into daily clinical practices through specific facilitation; a structured staff’s support system for emotional experiences. Discussion Self-care is an important enabler for the care of others. The core of our intervention was to encourage a meta-perspective in which the trainees developed greater perspicacity pertaining to their professional role in the working alliance and also recognizing the contribution of their personal emotions to impasse experienced with patients.